Metazoan parasite communities of the Pacific red snapper, Lutjanus peru (Perciformes: Lutjanidae): interannual variations in parasite communities. - Villalba-Vasquez, P.J., J. Violante-González, G. Pulido-Flores, S. Monks, A.A. Rojas-Herrera, P. Flores-Rodríguez, C.V. Cayetano, J.L. Rosas-Acevedo & N.G. Santos-Bustos (Journal of Helminthology, 2022)
Metazoan parasite communities can experience temporal structural changes related to seasonal and/or local variations in several biotic and abiotic environmental factors. However, few studies have addressed this issue in tropical regions, where changes in water temperature are less extreme than in temperate regions, so the factors or processes that can generate variations in these parasite communities are as yet unclear. We quantified and analysed the parasite communities of 421 Lutjanus peru (Nichols & Murphy, 1922) collected from Acapulco Bay in Guerrero, Mexico, over a four-year period (August 2018 to April 2021), to identify any interannual variation due to local biotic and abiotic factors influenced by natural oceanographic phenomena, such as El Nino-Southern Oscillation, or La Nina. Twenty-five metazoan parasite taxa were recovered and identified: seven Digenea species; two Monogenea; one Cestoda; one Acanthocephala; four Nematoda; and ten of Crustacea (seven Copepoda and three Isopoda). The digeneans and copepods were the best represented parasite groups. The parasite communities were characterized by a high numerical dominance of helminth larvae. Species richness at the component community level (13 to 19 species) was similar to reported richness in other Lutjanus spp. The parasite communities of L. peru had a high variability in species composition, but low aggregate variability (e.g. species diversity), suggesting that structure of these communities may be quite stable over time. A clear interannual variation pattern was not observed, suggesting that parasite species of this host may respond differently to variations in environmental factors. Interannual variations were possibly caused by a combination of biotic (i.e. host feeding behaviour and body size) and local abiotic factors (influenced by climatic anomalies) which generated notable changes in the infection levels of several component species.